2009
DOI: 10.1130/g25351a.1
|View full text |Cite
|
Sign up to set email alerts
|

A new look at old carbon in active margin sediments

Abstract: Recent studies suggest that as much as half of the organic carbon (OC) undergoing burial in the sediments of tectonically active continental margins may be the product of fossil shale weathering. These estimates rely on the assumption that vascular plant detritus spends little time sequestered in intermediate reservoirs such as soils, freshwater sediments, and river deltas , and thus only minimally contributes to the extraneously old 14

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 46 publications
2
38
0
Order By: Relevance
“…A number of other studies of the Mackenzie River system (on sediment and suspended OC) have reported similarly low radiocarbon contents ( Figure 6A; Goñi et al, 2005;Drenzek et al, 2007;Hilton et al, 2015;Vonk et al, 2015). This evidence, combined with low carbon preference index values (CPI) for n-alkanes extracted from Mackenzie River sediments (Yunker et al, 2002;Drenzek et al, 2009) suggests that the river carries significant amounts of sedimentary rock-derived "petrogenic" OC as well as pre-aged terrestrial (permafrost) OC that mixes with more modern plant-and minor contributions of algal-derived OC (Goñi et al, 2005;Drenzek et al, 2007;Hilton et al, 2015). The presence of such ancient OC likely at least partially accounts for the old age of the POC we sampled.…”
Section: Sources Of Oc To Suspended and Lower Delta (Lake Ld-1) Lake mentioning
confidence: 89%
“…A number of other studies of the Mackenzie River system (on sediment and suspended OC) have reported similarly low radiocarbon contents ( Figure 6A; Goñi et al, 2005;Drenzek et al, 2007;Hilton et al, 2015;Vonk et al, 2015). This evidence, combined with low carbon preference index values (CPI) for n-alkanes extracted from Mackenzie River sediments (Yunker et al, 2002;Drenzek et al, 2009) suggests that the river carries significant amounts of sedimentary rock-derived "petrogenic" OC as well as pre-aged terrestrial (permafrost) OC that mixes with more modern plant-and minor contributions of algal-derived OC (Goñi et al, 2005;Drenzek et al, 2007;Hilton et al, 2015). The presence of such ancient OC likely at least partially accounts for the old age of the POC we sampled.…”
Section: Sources Of Oc To Suspended and Lower Delta (Lake Ld-1) Lake mentioning
confidence: 89%
“…Vascular plant material is believed to spend little time sequestered in intermediate reservoirs such as soils, freshwater sediments, and river deltas and contributes minimally to the old 14 C ages often observed on continental shelves. This results in part from the large contribution of petrogenic relative to vascular plant material found in marine sediments (8). All the aforementioned TerrOC materials are important in regulating the global carbon and oxygen cycles.…”
mentioning
confidence: 99%
“…OC in Venice Cut and Nurse Slough, however, is considerably more depleted in 14 C. Bulk OC and < 1.6, 1.6 to 2.0, and 2.0 to 2.5 g cm −3 fractions are similar in radiocarbon isotope values ( 14 C −247 to −114 ‰) but high-density > 2.5 g cm −3 fractions are highly 14 C depleted ( 14 C −339 and −382 ‰, for Venice Cut and Nurse Slough, respectively) and hence the oldest (3300 and 3800 yr BP, respectively). Radiocarbon ages of sediments that are "too old" to reflect deposition of recently-biosynthesized ("young") OC require contributions from old OC (often termed "pre-aged" OC) from terrestrial soil or fossil (rock) OC (Drenzek et al, 2009;Griffith et al, 2010;Blair and Aller, 2012;Douglas et al, 2014;Galy et al, 2015) and/or anthropogenic (petrogenic or fossil fuel combustion) sources (Mitra et al, 2002;Masiello, 2004). Rivers are an important mechanism for redistributing old terrestrial OC (Raymond and Bauer, 2001b;Masiello and Druffel, 2001;Blair and Aller, 2012).…”
Section: Provenance Of Oc In the Sacramento-san Joaquin Deltamentioning
confidence: 99%